Rare Eccrine Porocarcinoma of The Eyelid in A Non-Caucasian Patient - Boesoirie, Shanti F.; Mardianty, Friska; Wahyu, Tri; Dewi, Niluh Putu Ayu; Nursalamah, Mia; Dahlan, Mohamad Rinaldi; Kartiwa, Raden Angga (Faculty of Medicine, Universitas Padjadjaran, 2025)
Eccrine porocarcinoma of the eyelid is a rare and locally aggressive tumor with a significant risk of metastasis and recurrence after surgical excision. There are only eight cases of eyelid porocarcinoma reported in the literature, most involve Caucasian patients. A 58-year-old non-Caucasian male had a recurrent mass of the left upper eyelid for a year. He underwent two prior mass removal procedures in the same location of the upper eyelid. At the time of this study, the patient underwent full-thickness excision, and a lateral canthal defect with superior palpebral involvement was sacrificed. The periosteal flap from the lateral orbital rim was attached to the edge of the intact tarsal plate of the upper eyelid as a part of the defect reconstruction. Good outcomes in terms of tumor recurrences, cosmesis, and upper eyelid functionality were observed one month following surgery. According to the histopathology, the tumor was identified as eccrine porocarcinoma, and the patient was recommended for chemotherapy. The 4-month follow-up showed no recurrence or metastasis. Eccrine porocarcinoma is a rare condition that should be taken into account when making a differential diagnosis for patient with malignant eyelid tumors. Wide excision is still a treatment of choice.